ASUHAN KEPERAWATAN PADA ANAK DENGAN DENGUE HEMORAGIC FEVER ( DHF ) - Welly Andria Mela Sari (Jurnal Ilmiah Cerebral Medika, 2019)
Dengue Hemorehagic Fever (DHF) or better known as Dengue Hemorrhagic Fever (DHF) is a fever accompanied by an enlarged liver and bleeding. This disease is caused by the dengue virus, a type of virus that is classified as an arbovirus and enters the patient's body through the bite of the aedes aegypti mosquito. The purpose of this literature study is to conduct a literature study exploring the management of nursing care with dengue hemorrhagic fever in adult males. This research design was prepared using a descriptive method approach. The data collection method used in this research is the documentation method. Based on the results of the study, data on An.R was 7 years old, where the child had a fever for more than 3 days, the child's mother said that An.R's body temperature was hot, namely a body temperature of 38.5 ˚C, headache, no appetite, nausea, vomiting, pain when swallowing , weakness, muscle and joint pain.